The vase life of waxflower (Chamelaucium Desf.) is affected by the weight ratio of flowers to stem - Dung, C.; Seaton, K.; Singh, Zora (Polskie Towarzystwo Nauk Ogrodniczych, 2016)
The effect of flower weight on changes in the vase life of flowers and leaves of waxflowers was studied by evaluating the arranged flower weight of cultivars derived from the Chamelaucium uncinatum, Chamelaucium megalopetalum and Verticordia species. Competition for water and carbohydrates between flowers and leaves influenced vase life. The removal of flowers had at least four times the effect on leaf vase life as the removal of leaves on flower vase life. Supplying exogenous sucrose to satisfy the demand for carbohydrates negated this effect, indicating that flowers depend on carbohydrates being supplied from leaves to maintain vase life. Cultivars with a greater proportion of flowers (on a weight basis) improved the vase life of flowers at the expense of the leaves. Cultivars with large flowers or many small flowers or a greater weight ratio of flowers to stem appeared to draw more carbohydrates and water from the leaves, giving them a longer vase life and decreasing the vase life of the leaves. The vase life of flowers increased with the stage of opening of flowers up to 50% opening and then decreased up to 100% opening.